2017
DOI: 10.1093/annweh/wxx076
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Manganese and Fine Motor Skills in Elderly Men: Results from the Heinz Nixdorf Recall Study

Abstract: We found evidence that exposure to inhalable Mn may carry a risk for dexterity deficits. Whether these deficits can be exclusively attributed to Mn remains to be elucidated, as airborne Mn is strongly correlated with iron in metal fumes, and high ferritin was also associated with errors in line tracing. Furthermore, hand training effects must be taken into account when testing for fine motor skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…In contrast, differences in fine motor tests were less pronounced although PD patients displayed larger amplitudes and lower tapping speed than controls in line with other investigations [32,33]. In a large cohort of healthy subjects, we have demonstrated that age is a strong determinant of dexterity [11]. This was not as obvious in this study population, where the mixed PD phenotype and the left or more affected hand were stronger predictors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, differences in fine motor tests were less pronounced although PD patients displayed larger amplitudes and lower tapping speed than controls in line with other investigations [32,33]. In a large cohort of healthy subjects, we have demonstrated that age is a strong determinant of dexterity [11]. This was not as obvious in this study population, where the mixed PD phenotype and the left or more affected hand were stronger predictors.…”
Section: Discussionsupporting
confidence: 88%
“…Dexterity was tested for the right and left hand with a tapping test. Tapping hits were determined with the Motor Performance Series (Schuhfried, Mödling, Austria) as previously described [11]. The number of hits, a measure of motor speed, was acquired by tapping a stylus within 32 s as often as possible on a 1600 mm 2 plate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, excessive occupational exposure may also occur, which can lead to manganese overload with severe side effects, clinically known as manganism. Individuals who have an increased risk of being exposed to higher than normal levels of manganese include workers in the production of iron and steel, dry cell batteries, fuel oil additives and antiknock agents, glasses, potassium permanganate, fungicides, and leather tanning [19][20][21]. The neurological symptoms of manganism consist of reduced response speed, irritability, intellectual deficits, mood changes, compulsive behaviors in the initial stages of the disorder, and more prominent and irreversible extrapyramidal dysfunction resembling Parkinson's disease upon protracted exposure [22,23].…”
Section: Introductionmentioning
confidence: 99%